Analysis of the Jiwasraya Case - Sahrul, Farhan Ananda; Lie, Gunardi (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to examine one case of financial report manipulation or fraud that has occurred in Indonesia, namely PT. Jiwasraya Insurance (Persero). This research uses a qualitative method, where this research uses a type of research that produces descriptive data and/or results in the form of written or spoken words from what is observed. The results of this research indicate that PT. Jiwasraya Insurance (Persero) was proven to have committed fraud by fulfilling several aspects such as the category of fraud, the results of analysis of the geographic location or industry where the fraud occurred, the profile of the victims and perpetrators of the fraud, the motivation of the perpetrators of the fraud, the impact of the fraud, and strategies for detecting fraud. The results of this research show that fraud can involve and harm many parties, so this research is expected to motivate companies to improve the company's internal control against fraud that is prone to occur.